تأثير موعد الزراعة في إنتاج الشتول، و النمو و الإزهار للصنف المدخل Canneto White من نبات المنثور (Matthiola incana L.) - نصور, مازن (Latakia University Journal -Biological Sciences Series, 2019)
The aim of this research was to study the influence of different sowing dates on some germination parameters, seedling quality, and on growth and flowering of Stock (Matthiola incana, cv. Canneto White). The experiment was carried out at nursery and laboratories of Agriculture Faculty, Tishreen University during two seasons (from 2016 to 2018), and included five sowing dates (D1: 10 September, D2: 30 September, D3: 20 October, D4: 10 November, and D5: 30 November) with three replicates (90 seeds by date). The results showed the success of cultivation of Stock (Canneto White) in different dates, both in the production of seedlings with good quality, or give a floral production with suitable specifications. The germination parameters and seedling quality were significantly responded to sowing date, and maximum values were obtained from (D1, D2). Planting in early dates led to an increase in the vegetative parameters (plant height, leaves area and chlorophyll content). In other hand, the best flowering parameters (flowering initiation, spike length, number of flowers on spike, and flower diameter) were obtained with D1 and D2 هدف هذا البحث إلى دراسة تأثير موعد زراعة البذور في بعض مؤشرات الإنبات و نوعية الشتول الناتجة، بالإضافة إلى تأثيره في بعض مؤشرات النمو الخضري و الزهري لنبات المنثور. نفذ البحث في مشتل ومخابر كلية الزراعة بجامعة تشرين و لموسمين زراعيين (من 2016 حتى 2018). تضمنت التجربة خمسة مواعيد زراعة: 10 أيلول، 30 أيلول، 20 تشرين الأول، 10 تشرين الثاني و30 تشرين الثاني، و بثلاث مكررات و بمعدل 90 بذرة لكل موعد. بينت نتيجة الدراسة نجاح زراعة صنف المنثور المدخل (Canneto White) في مواعيد مختلفة، سواء في إنتاج شتول بنوعية جيدة، أو في إعطاء إنتاج زهري بمواصفات مرغوبة. أشارت النتائج إلى تأثير موعد الزراعة في كل من مؤشرات الانبات و نوعية الشتول الناتجة و بفروق معنوية، وحقق الموعدان 10 و 30 أيلول أفضل النتائج. كما بينت النتائج التأثير الإيجابي للزراعة المبكرة في مؤشرات النمو الخضري (طول النبات، مساحة المسطح الورقي و كمية الكلوروفيل الكلي)، بالإضافة إلى تشكل الشماريخ الزهرية وتطورها (موعد الإزهار, طول الشمراخ الزهري, عدد الأزهار ومتوسط قطر الزهرة).